Keterbukaan Informasi Publik dalam Penyelenggaraan Pemilu di Indonesia - Oktaviane, Diga Putri; Mardin, Aznil; Helmi, Rahmadhona Fitri (Faculty of Social Science, Universitas Negeri Padang, 2024)
The General Election Commission is a national, permanent and independent election management institution tasked with carrying out elections. Law Number 14 of 2008 concerning Openness of Public Information (KIP) is a path towards an era of open information and transparent and responsible state administration which is formally guaranteed in national law. Openness of public information is important in elections in order to build a government system in the future. The aim of this research is to determine the role and efforts made by the KPU in providing information to the public in order to realize openness of public information in the implementation of elections. This research uses a qualitative method where the results obtained are in the form of descriptive data written based on sources obtained from books, theses, journals and articles. From the research conducted, it was found that the KPU is a non-partisan government institution tasked with election activities and has been mandated in Law no. 15 of 2011 concerning holding national and local general elections. Efforts that the KPU can make include creating a website to provide information to the public periodically and at any time.